Case Report: Membranous nephropathy associated with mantle cell lymphoma: a rare case - Ren, Mian; Cao, Luxi; Shen, Quanquan; Zhu, Bin; Wu, Juan (Frontiers in Medicine, 2025)
Mantle cell lymphoma (MCL) is a rare, aggressive non-Hodgkin lymphoma (NHL) that can affect the kidneys. In this research, we described a very rare case of secondary membranous nephropathy (MN) associated with MCL. A 67-year-old man manifested with impaired renal function and nephrotic syndrome (NS). Kidney biopsy revealed atypical MN and MCL cell infiltration. After eight rounds of modified R-CHOP therapy, which includes rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone, the patient achieved complete remission, accompanied by improved renal function and a reduction in proteinuria. This case demonstrates the precise diagnosis and treatment of the primary disease, which can lead to favorable outcomes.